A new species of the genus Phyllodesma (Phyllodesma) Hübner, [1820] 1816 from southern China (Lepidoptera: Lasiocampidae) - Saldaitis, Aidas; Zolotuhin, Vadim V. (Zootaxa, 2018)
A new species, Phyllodesma kopetzi sp. nov. (type locality: China, W. Sichuan, Road Daocheng/Litang, 4100 m, N29°36.788’, E100°19.825’), is described from the southwestern part of China’s Sichuan Province. The holotype is deposited in the World Insect Gallery (Joniškis, Lithuania) collection. It is compared with the poorly known Phyllodesma sinina (Grum-Grshimailo, 1891) described from Sinin-Shan [Qinghai, China].